The Effect of menopause on Lipid Profile Indices in Derna City - Alshuwayhidi , Adham; Lajahr , Salma; Albhori , Sara (Libyan Journal of Medical and Applied Sciences, 2025)
Menopause-associated dyslipidemia, is a risk factor for cardiovascular and cerebrovascular diseases. Examining lipid profile in menopause is crucial to assess dyslipidemia and estimate risk of future atherogenic events. The objective of this study is to assess the effect of menopause on lipid profile indices. A cross-sectional study was conducted in the city of Derna, Libya, including 34 purposely selected apparently healthy females, of which 18 were postmenopausal and 16 were premenopausal women. Fasting blood was collected after obtaining informed consent form the participants. Serum total cholesterol (TC), triglycerides (TG), low density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) were measured by a chemical analyzer. Very low-density lipoprotein cholesterol (VLDL-C) was calculated by Friedewald formula. No statistically significant differences were found between the two groups in BMI or any of the lipid profile indices (p > 0.05). Postmenopausal women exhibited non-significantly higher levels of TG (102.31 ± 59.67 vs. 83.05 ± 33.90 mg/dL) and VLDL-C (20.46 ± 11.93 vs. 16.61 ± 6.78 mg/dL), and lower HDL-C levels (47.85 ± 18.20 vs. 54.23 ± 1.29 mg/dL). Interestingly, TC and LDL-C levels were slightly higher in premenopausal women but also without statistical significance. Menopause seems to have no impact on lipid profile. Larger research involving polycentric trials that can provide a nation comprehensive profile for proper management of dyslipidemia and its atherogenic events during postmenopasue is needed.